2006
DOI: 10.1111/j.1423-0410.2006.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Massive blood transfusion and outcome in 1062 polytrauma patients: a prospective study based on the Trauma Registry of the German Trauma Society

Abstract: Massive blood transfusion is one main prognostic factor for mortality in trauma. Although MBT is generally considered to be critical, every second trauma patient with MBT survived. A cut-off value for the number of PRBC could not be determined. Extended transfusion management even with high amounts of PRBC seems to be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
80
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 73 publications
3
80
2
3
Order By: Relevance
“…Overall, our data suggest that early massive transfusion is associated with worse organ dysfunction in the ICU, but not increased early mortality or hospital mortality among those surviving initial resuscitation. In contrast, other studies in traumatically injured patients have found an independent association of red blood cell transfusion on mortality, 10,[17][18][19][20]26 with most hemorrhage-related deaths occurring within 24 hr of trauma. 4 This association has been described in patients with primarily blunt trauma 10,19 and in mixed populations with *20% penetrating trauma.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…Overall, our data suggest that early massive transfusion is associated with worse organ dysfunction in the ICU, but not increased early mortality or hospital mortality among those surviving initial resuscitation. In contrast, other studies in traumatically injured patients have found an independent association of red blood cell transfusion on mortality, 10,[17][18][19][20]26 with most hemorrhage-related deaths occurring within 24 hr of trauma. 4 This association has been described in patients with primarily blunt trauma 10,19 and in mixed populations with *20% penetrating trauma.…”
Section: Discussionmentioning
confidence: 50%
“…In contrast, other studies in traumatically injured patients have found an independent association of red blood cell transfusion on mortality, 10,[17][18][19][20]26 with most hemorrhage-related deaths occurring within 24 hr of trauma. 4 This association has been described in patients with primarily blunt trauma 10,19 and in mixed populations with *20% penetrating trauma. 17,18,20 These studies have also demonstrated patient age and severity of injury and illness to predict hospital mortality, raising the possibility 21 HR \ 1 implies a decreased relative hazard of live ICU discharge, that is, a longer ICU stay among survivors as the value of the predictor variable increases.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations